2014
DOI: 10.1063/1.4894631
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/GeOx gate stack on germanium substrate fabricated by in situ cycling ozone oxidation method

Abstract: Al2O3/GeOx/Ge gate stack fabricated by an in situ cycling ozone oxidation (COO) method in the atomic layer deposition (ALD) system at low temperature is systematically investigated. Excellent electrical characteristics such as minimum interface trap density as low as 1.9 × 1011 cm−2 eV−1 have been obtained by COO treatment. The impact of COO treatment against the band alignment of Al2O3 with respect to Ge is studied by x-ray photoelectron spectroscopy (XPS) and spectroscopic ellipsometry (SE). Based on both XP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…This COO method is proved to be effective in repairing the defects like OH-related groups to suppress the gate leakage current. The minimum it value of 1.9 × 10 11 cm −2 eV −1 is obtained by inserting GeO passivation layer with the COO treatment, as shown in Figure 14 [47].…”
Section: Ozonementioning
confidence: 98%
See 3 more Smart Citations
“…This COO method is proved to be effective in repairing the defects like OH-related groups to suppress the gate leakage current. The minimum it value of 1.9 × 10 11 cm −2 eV −1 is obtained by inserting GeO passivation layer with the COO treatment, as shown in Figure 14 [47].…”
Section: Ozonementioning
confidence: 98%
“…For high-pressure oxidation and plasma postoxidation techniques, both of them can obtain a relatively low minimum value of it in the order of 10 11 cm −2 eV −1 even at a thin EOT of subnanometer [12,38]. For ozone postoxidation technique, a relatively low minimum value of it of 1.9 × 10 11 cm −2 eV −1 was also obtained under a relatively thick EOT (definite data not given in their report) [47]. Thus, these three techniques are all potential methods to improve the interfacial properties of Ge/dielectric gate stack in Ge MOSFETs.…”
Section: Conclusion and Further Outlookmentioning
confidence: 98%
See 2 more Smart Citations
“…A high quality Ge MOS gate stacks with low interface state density (D it ) is imperative for the successful industrial application [2]. After about 15 years′ intensive studies [3][4][5], it has been demonstrated that Ge dioxide or sub-oxide (GeO x ) can provide excellent electrical properties with the D it in the range of 10 10 -10 11 cm -2 ·eV -1 [6][7][8][9][10][11][12][13][14][15][16][17]. And the GeO x can be grown by thermal oxidation in atmospheric pressure O 2 [6; 7], high pressure O 2 (~70 atm) [13; 14], oxygen plasma [9-12; 17], or ozone oxidation [8; 15; 16].…”
Section: Introductionmentioning
confidence: 99%